- Trending Categories
- Data Structure
- Networking
- RDBMS
- Operating System
- Java
- iOS
- HTML
- CSS
- Android
- Python
- C Programming
- C++
- C#
- MongoDB
- MySQL
- Javascript
- PHP

- Selected Reading
- UPSC IAS Exams Notes
- Developer's Best Practices
- Questions and Answers
- Effective Resume Writing
- HR Interview Questions
- Computer Glossary
- Who is Who

In this method, we try to remove all the ε-transitions from the given Non-deterministic finite automata (NFA) −

The method is mentioned below stepwise −

**Step 1**− Find out all the ε-transitions from each state from Q. That will be called as ε-closure(qi) where, qi ∈Q.**Step 2**− Then, ๐ฟ1 transitions can be obtained. The ๐ฟ1 transitions means an ε-closure on ๐ฟ moves.**Step 3**− Step 2 is repeated for each input symbol and for each state of given NFA.**Step 4**− By using the resultant status, the transition table for equivalent NFA without ε can be built.

NFA with ε to without ε is as follows −

δ1(q,a) = ∈ - closure (δ (δ∈^(q,∈๐),a)) where, δ^(q,∈๐) = ∈ - closure(q)

Convert the given NFA with epsilon to NFA without epsilon.

We will first obtain ε-closure of each state i.e., we will find ε-reachable states from the current state.

Hence,

- ε-closure(q0) = {q0,q1,q2}
- ε-closure(q1) = {q1,q2}
- ε-closure(q2) = {q2}

ε-closure(q0) means with null input (no input symbol) we can reach q0, q1, q2.

In a similar manner for q1 and q2 ε-closure are obtained.

Now we will obtain ๐ฟ1 transitions for each state on each input symbol as shown below −

δ'(q0, 0) = ε-closure(δ(δ^(q0, ε),0)) = ε-closure(δ(ε-closure(q0),0)) = ε-closure(δ(q0,q1,q2), 0)) = ε-closure(δ(q0, 0) ∪ δ(q1, 0) U δ(q2, 0) ) = ε-closure(q0 U Φ ∪ Φ) = ε-closure(q0) = {q0,q1, q2} δ'(q0, 1) = ε-closure(δ(δ^(q0, ε),1)) = ε-closure(δ(q0,q1,q2), 1)) = ε-closure(δ(q0, 1) ∪ δ(q1, 1) U δ(q2, 1) ) = ε-closure(Φ ∪q1 U Φ) = ε-closure(q1) = {q1, q2} δ'(q0, 2) = ε-closure(δ(δ^(q0, ε),2)) = ε-closure(δ(q0,q1,q2), 2)) = ε-closure(δ(q0, 2) ∪ δ(q1, 2) U δ(q2, 2) ) = ε-closure(Φ U ΦU q2) = ε-closure(q2) = {q2} δ'(q1, 0) = ε-closure(δ(δ^(q1, ε),0)) = ε-closure(δ(q1,q2), 0)) = ε-closure(δ(q1, 0) U δ(q2, 0) ) = ε-closure(Φ ∪ Φ) = ε-closure(Φ) = Φ δ'(q1,1) = ε-closure(δ(δ^(q1, ε),1)) = ε-closure(δ(q1,q2), 1)) = ε-closure(δ(q1, 1) U δ(q2, 1) ) = ε-closure(q1 ∪ Φ) = ε-closure(q1) = {q1,q2} δ'(q1, 2) = ε-closure(δ(δ^(q1, ε),2)) = ε-closure(δ(q1,q2), 2)) = ε-closure(δ(q1, 2) U δ(q2, 2) ) = ε-closure(Φ ∪ q2) = ε-closure(q2) = {q2} δ'(q2, 0) = ε-closure(δ(δ^(q2, ε),0)) = ε-closure(δ(q2), 0)) = ε-closure(δ(q2, 0)) = ε-closure(Φ) = Φ δ'(q2, 1) = ε-closure(δ(δ^(q2, ε),1)) = ε-closure(δ(q2), 1) = ε-closure(δ(q2, 1)) = ε-closure(Φ) = Φ δ'(q2, 2) = ε-closure(δ(δ^(q2, ε),)) = ε-closure(δ(q2), 2)) = ε-closure(δ(q2, 2)) = ε-closure(q2) = {q2}

Now, we will summarize all the computed δ' transitions as given below −

δ'(q0,0)={q0,q1,q2} δ'(q0,1)={q1,q2} δ'(q0,2)={q2} δ'(q1,0)= { Φ } δ'(q1,1)={q1,q2} δ'(q1,2)={q2} δ'(q2,0)={ Φ } δ'(q2,1)={ Φ } δ'(q2,2)={q2}

The **transition table** is given below −

States\inputs | 0 | 1 | 2 |
---|---|---|---|

q0 | {q0,q1,q2} | {q1,q2} | {q2} |

q1 | Φ | {q1,q2} | {q2} |

q2 | Φ | Φ | {q2} |

The NFA without epsilon is given below −

Here, q0, q1, q2 are final states because ε-closure(q0), ε-closure(q1) and ε-closure(q2) contain a final state q2.

- Related Questions & Answers
- How to convert NFA with epsilon to DFA in TOC?
- Explain NFA with epsilon transition.
- What is an acceptance of language by NFA with Epsilon?
- Construct NFA with Epsilon moves for regular expression a+ba*.
- What is an epsilon closure in TOC?
- Explain the elimination of epsilon productions in CFG
- Explain with an example how to convert NFA to DFA.
- Eliminate epsilon, unit and useless symbols and rewrite into CNF
- How to convert from NFA to DFA in TOC?
- Find FIRST & FOLLOW for the following Grammar\nE → TE′\nE → +TE′|ε\nT → FT′\nT′ →* FT′|ε\nF → (E)|id
- Convert NFA to DFA and explain the difference between them
- Find FIRST & FOLLOW for the following Grammar.\nS → A a A | B b B\nA → b B\nB → ε
- Write a C program to convert uppercase to lowercase letters without using string convert function
- C program to simulate Nondeterministic Finite Automata (NFA)
- How to convert Python datetime to epoch with strftime?

Advertisements